Facile one‐step hydrothermal syntheses of graphene oxide–MnO2 composite and their application in removing heavy metal ions. (1st August 2018) - Liang, Chunyan; Feng, Xuezhen; Yu, Jingang; Jiang, Xinyu
Abstract : In this work, a composite of graphene oxide (GO) supported by granulated manganese dioxide (MnO2 ) has been synthesised via a facile one‐step hydrothermal process and then used as adsorbent to remove heavy metal ions from aqueous solution. The morphology and surface functional groups of GO–MnO2 composite were characterised by Fourier transform infrared spectroscopy, Raman spectra, X‐ray photoelectron spectroscopy, scanning electron microscopy and thermogravimetric analysis. The results indicated that MnO2 particles were successfully inserted into graphene sheets, and the agglomeration of GO was prevented. The effects of contact time and initial concentrations of heavy metal ions on the adsorption capacity of GO–MnO2 composite were studied. The adsorption data fitted well with the pseudo‐second‐order kinetic model and the Langmuir isotherm model. The maximum adsorption capacity for Pb 2+ obtained from Langmuir isotherm model was about 490 mg/g. Based on the results from the removal of four heavy metal ions from smelting wastewater and the reusability experiments, it could be deduced that GO–MnO2 composite is a potential adsorbent for environmental clean‐up.